The Voyage of the Dawn Treader - Lewis, C. S., (Clive Staples), 1898-1963, author 208114; Baynes, Pauline, illustrator 338619 (London, England : HarperCollins Children's Books, 2010)
Lucy and Edmund, stuck with their awful cousin Eustace, suddenly find themselves on board the Dawn Treader - and realise they have fallen into the magical land of Narnia. Reunited with old friends, the young King Caspian and Reepicheep the mouse, they gladly join the voyage World's End. Eustace, however, is not so happy...